2003
DOI: 10.1124/jpet.103.056705
|View full text |Cite
|
Sign up to set email alerts
|

The Thromboxane Receptor Antagonist PBT-3, a Hepoxilin Stable Analog, Selectively Antagonizes the TPα Isoform in Transfected COS-7 Cells

Abstract: The hepoxilin analog PBT-3 [10(S)-hydroxy-11,12-cyclopropyleicosa-5Z,8Z,14Z-trienoic acid methyl ester] was previously shown to inhibit the aggregation of human platelets and to antagonize the binding of the thromboxane receptor agonist I-BOPin human platelets (Pace-Asciak et al., 2002). We show herein that PBT-3 inhibits, to different degrees, binding of the TP receptor antagonist, to the TP receptor isoforms in TP␣-and TP␤-transfected COS-7 cells. These isoforms possess a different tail length, the ␣ being s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…showed that the hepoxilin analogue, PBT‐3 [10(S)‐hydroxy‐11,12‐cyclopropyleicosa‐5(Z),8(Z),14(Z)‐trienoic acid methyl ester] inhibited binding of the TP antagonist [ 3 H]‐SQ29548 to TP α , but not TP β , receptors in transiently transfected COS‐7 cells (Qiao et al . ). These data and ours indicate that the structure around carbon 11 and 12 may vary greatly and still inhibit TP receptors.…”
Section: Discussionmentioning
confidence: 97%
“…showed that the hepoxilin analogue, PBT‐3 [10(S)‐hydroxy‐11,12‐cyclopropyleicosa‐5(Z),8(Z),14(Z)‐trienoic acid methyl ester] inhibited binding of the TP antagonist [ 3 H]‐SQ29548 to TP α , but not TP β , receptors in transiently transfected COS‐7 cells (Qiao et al . ). These data and ours indicate that the structure around carbon 11 and 12 may vary greatly and still inhibit TP receptors.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the exact physiological significance of the existence of two iso- forms is still unclear, although it has been shown that TP␣ was the only isoform expressed in platelets (Habib et al, 1999) and that both TP␣ and TP␤ were expressed in smooth muscle cells (Miggin and Kinsella, 1998). Recently, Qiao et al (2003) showed for the first time that the hepoxilin-stable analog PBT-3 could selectively bind the TP␣ isoform in transfected COS-7 cells. Thus, we postulated that BM-613 could have a greater affinity for TP␣ than TP␤ and that this could be coupled with higher activity as an antiplatelet agent.…”
Section: Bm-613 An Original Antiplatelet and Antithrombotic Agent 297mentioning
confidence: 99%
“…PBT-3 was the most active of the PBTs showing 5-10 fold greater activity in inhibiting platelet aggregation than the next best PBTs. Further studies using COS-7 cells in which transient expression of the TPα and TPβ receptor were carried out, showed a greater specificity for PBT-3 for the TPα receptor, the isoform abundantly present in human platelets [39]. These findings demonstrate a potentially important and powerful action of PBT-3 as an antagonist of the TP receptor revealing a likely mechanism for its inhibitory actions on platelet aggregation.…”
Section: Anti-thrombotic Actionsmentioning
confidence: 91%